Influence of Regular Astigmatism on the Human Visual Cortex. A Functional Magnetic Resonance Imaging Study - Takuya SHIBA; Hiroshi TSUNEOKA (Journal of Ophthalmic Science, 2015)
Purpose: To describe a new functional magnetic resonance imaging (fMRI) method for measuring the influence of regular astigmatism, both against-the-rule (ATR) and with-the-rule (WTR), on the human visual cortex. Setting: Department of Ophthalmology, Jikei University School of Medicine, Tokyo, Japan. Design: Experimental study. Methods: Images were acquired in two healthy volunteers using a 1.5 T scanner equipped for echo planar imaging. Horizontal and vertical sine wave grating flickering at a frequency of 8 Hz were simultaneously presented during the 20-second stimulation period. During the control period , subjects fixated on a control target. Stimulations were performed under three different conditions that included with hard contact lenses that were equal to emmetropia without astigmatism (condition 1); with hard contact lenses and cylindrical glasses of +6.00D at 0°, imitating WTR (condition 2); and with hard contact lenses and cylindrical glasses of +6. 00 D at 90°, imitating ATR (condition 3). Raw data were processed using in-house software with the significance of activation determined by Statistical Parametric Mapping (SPM 99). Results: Although higher activation was found in the primary visual cortex for condition 1 versus conditions 2 and 3, activation in the dorsal pathway was higher in conditions 2 and 3 compared to condition 1. Dorsal pathway activation was also higher in condition 3 versus condition 2. Conclusions: Study findings showed the potential influence of ATR and WTR on the human visual cortex , with fMRI able to detect the influence of regular astigmatism on the visual cortex. Our current results suggest that fMRI may be useful in exploring the influence of astigmatism on vision.
Keywords: astigmatism